Athlete mental health: How coaches can help - Schwartz, V. (Olympic & Paralympic Coach, 2020)
When thinking about mental health, athletes - and especially elite athletes - present us with a com-plicated story. On the one hand, research carried out by the NCAA suggests that in many respects, from a mental health perspective, competitive athletes are a robust and resilient group. Rates of mental health problems among college student-athletes are similar to or lower than college students in general. There are a few exceptions, such as having higher rates of gambling and, among women athletes, higher incidence of eating disorders. Nevertheless, elite/competitive athletes experience unique stressors that put them at higher risk for emotional challenges. Intense competition, risk and experience of potential career-ending injuries, long periods of travel away from home and sleep dis-ruptions, the stresses of intense training can all present athletes with significant challenges. Coaches and trainers have close relationships with athletes and, thus, are uniquely well placed to notice, sup-port and refer athletes who might be experiencing an emotional challenge. This does not require deep technical knowledge or skill and whether you realize it or not, you already know how to do this.